Patterns of light : chasing the spectrum from Aristotle to LEDs - Beeson, Steven. (Springer, 2017)
Begins by addressing properties of light as seen in the everyday world: events such as refraction in a pool, lenses in the form of glasses, the colors of objects, atmospheric events, and more. This title includes chapters that explain these events at the atomic and subatomic level.